1998
DOI: 10.1128/mcb.18.8.4689
|View full text |Cite
|
Sign up to set email alerts
|

CDC42 and FGD1 Cause Distinct Signaling and Transforming Activities

Abstract: Activated forms of different Rho family members (CDC42, Rac1, RhoA, RhoB, and RhoG) have been shown to transform NIH 3T3 cells as well as contribute to Ras transformation. Rho family guanine nucleotide exchange factors (GEFs) (also known as Dbl family proteins) that activate CDC42, Rac1, and RhoA also demonstrate oncogenic potential. The faciogenital dysplasia gene product, FGD1, is a Dbl family member that has recently been shown to function as a CDC42-specific GEF. Mutations within the FGD1 locus cosegregate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 65 publications
2
39
0
Order By: Relevance
“…The dominant-negative mutant, TC10T31N, suppressed the focus formation ability of these cells. These observations are similar to those obtained for Cdc42, Rac1, RhoA and RhoB (Prendergast et al, 1995;Qiu et al, 1995Qiu et al, , 1997Osada et al, 1997;Westwick et al, 1997;Whitehead et al, 1998). Moreover, previous studies indicated that the constitutively active mutants of Cdc42 (G12V) and Rac (G12V) increased the colony formation ability of mammalian fibroblast cell lines in soft agar.…”
Section: Tc10 Contributes To V-rel-mediated Transformationsupporting
confidence: 89%
“…The dominant-negative mutant, TC10T31N, suppressed the focus formation ability of these cells. These observations are similar to those obtained for Cdc42, Rac1, RhoA and RhoB (Prendergast et al, 1995;Qiu et al, 1995Qiu et al, , 1997Osada et al, 1997;Westwick et al, 1997;Whitehead et al, 1998). Moreover, previous studies indicated that the constitutively active mutants of Cdc42 (G12V) and Rac (G12V) increased the colony formation ability of mammalian fibroblast cell lines in soft agar.…”
Section: Tc10 Contributes To V-rel-mediated Transformationsupporting
confidence: 89%
“…GTPase defective TC10 synergizes with an activated Raf-1 kinase to transform NIH3T3 cells Activated (GTPase defective) forms of Rac1, RhoA, or CDC42 show little or no focus-forming activity when assayed in NIH3T3 ÂŽbroblasts. However, activated versions of all three proteins cooperate with activated forms of the Raf-1 serine/threonine protein kinase and exhibit synergistic focus forming activity in rodent ÂŽbroblast transfection assays (Westwick et al, 1997;Whitehead et al, 1998). Therefore, we wanted to determine if activated TC10 also possesses transforming potential.…”
Section: Tc10 Is a Member Of The Rho Family Of Ras-related Gtpasesmentioning
confidence: 99%
“…JNK activation, in turn, results in the phosphorylation and activation of the transcription factors c-Jun and Elk-1, which stimulate transcription from genes containing AP-1 and SRE elements, respectively (Joneson et al, 1996;Lamarche et al, 1996;Westwick et al, 1997; for review see Wasylyk et al, 1998). Further supporting a role for CDC42 and Rac in JNK signaling, JNK and cJun are activated in cells over-expressing GEFs that act on Rac and CDC42 (Westwick et al, 1998;Whitehead et al, 1998;Zhou et al, 1998).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The pAX142-lacZ reporter plasmid (39) was included in the transfection mix and ␤-galactosidase activity was measured. The pAX142 promoter has been reported previously to be unaffected by Dbl family proteins (39,45).…”
Section: Hiv-1 Production and Replication In Transfected Human Cellsmentioning
confidence: 99%